Two new wood-inhabiting fungal species (Polyporales, Basidiomycota) from Yunnan Province, China - Wang, Lu; Su, Jiangqing; Muhammad, Akmal; Zhao, Changlin (Phytotaxa, 2024)
Wood-inhabiting fungi are a cosmopolitan fungal group worldwide. Two new wood-inhabiting fungal species, Rhodoantrodia purpurascens and Steccherinum wumengshanense are proposed based on a combination of the morphological features and molecular evidence. Rhodoantrodia purpurascens is characterized by the corky basidiomata with a pale lilac to lavender pore surface, a dimitic hyphal system with clamped generative hyphae, and broadly ellipsoid basidiospores. Steccherinum wumengshanense is characterized by the corticoid basidiomata having a white to cream hymenial surface, a monomitic hyphal system with clamp generative hyphae, and ellipsoid basidiospores. Full descriptions, photo plates and phylogenetic analysis results of the new species are provided.